TEACHING YOUNG LEARNERS WITH THE USE OF TRADITIONAL GAMES - Madina Ulugbek kizi Muhammadova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study explores teaching English vocabulary to young learners through the traditional game “hide and seek.” It highlights reducing gadget use, promoting cultural values, and creating an engaging learning environment by integrating play-based methods into early childhood education.